Development of ischemia/reperfusion tolerance in the rat small intestine. An epithelium-independent event. - Osborne, D L (1994)
In stable organ systems, such as the heart and kidneys, an oxidant stress induces an increase in endogenous antioxidant systems resulting in an increased resistance of the tissue to a subsequent oxidant challenge. The development of this oxidant tolerance requires 1.5-6 d. The aim of the present study was to determine whether oxidant tolerance can be induced in the small intestinal mucosa, a labile system whose epithelium turns over every 2-3 d. Ischemia/reperfusion-induced epithelial barrier dysfunction of the small intestinal mucosa was monitored in Sprague-Dawley rats whose intestines had been exposed to an ischemic insult 1, 24, or 72 h previously. At 24 h, but not 1 or 72 h after the initial ischemic insult, the mucosa was more resistant to ischemia/reperfusion-induced barrier dysfunction. The antioxidant status of the mucosa was enhanced at 24 h, but not at 1 or 72 h after the initial ischemic insult. This adaptation appears to be specific for oxidants, since an initial ischemic insult imposed 24 h earlier also protected against H2O2-induced, but not acid- or ethanol-induced, barrier dysfunction. Further studies indicated that the increase in antioxidant status of the mucosa observed 24 h after the initial ischemic insult was a result of adaptational changes in the lamina propria, rather than the epithelium. In vitro studies with isolated epithelial cells also indicated that epithelial cells do not develop oxidant tolerance. We conclude that the development of oxidant tolerance in the small intestinal mucosa does not involve an active participation of the epithelial lining.